Ionospheric response to 2009 sudden stratospheric warming in the Northern Hemisphere. Issue 12 (5th December 2014) - Oyama, K.‐I.; Jhou, J. T.; Lin, J. T.; Lin, C.; Liu, H.; Yumoto, K.
Abstract We study the behavior of the F region ionosphere in the Northern Hemisphere during the sudden stratospheric warming period of 19–30 January 2009 by using FORMOSAT‐3/Constellation Observing System for Meteorology, Ionosphere, and Climate (COSMIC) ionosphere data (NmF2, hmF2, and height profile). We concentrated our study in the longitude bands 30°E–30°W, as well as 150°E–150°W, where no detailed study has been reported so far. At low magnetic latitude, the NmF2 decreases except during 09–12 LT: in the latitude zone of 20–40° NmF2 shows an increase of 30% during 09–12 LT. At higher magnetic latitude the NmF2 shows an increase during daytime and a reduction in the evening (21–03 LT). There is a latitude zone where NmF2 does not change. The latitude seems to correspond to the latitude where atmospheric temperature does not change. The behavior of the NmF2 seems to suggest a reduction of neutral density in low latitude and increase of neutral density in higher latitude. During the period of day of year (DOY) 25–31, the NmF2 shows a drastic reduction only during 06–09 LT in low latitudes, which is slightly away from geomagnetic equator. This special feature which occurred during declining phase of the sudden stratospheric warming (SSW) might be explained as due to enhanced dynamo electric field. The study suggests global change of the thermosphere including dynamo region, in spite of the fact that SSW is a high‐latitude phenomenon which occurred much below the height region of thermosphere.